Violympic toán 7

PA

cho a,b,c là ba số thực khác khác 0 tm đk \(\dfrac{a+b-c}{c}=\dfrac{b+c-a}{a}=\dfrac{c+a-b}{b}\)

hãy tính \(b=\left(1+\dfrac{b}{a}\right)\left(1+\dfrac{a}{c}\right)\left(1+\dfrac{c}{b}\right)\)

VT
13 tháng 2 2018 lúc 19:38

Ta có : \(\dfrac{a+b-c}{c}=\dfrac{b+c-a}{a}=\dfrac{c+a-b}{b}\)

\(\Leftrightarrow\dfrac{a+b-c}{c}+2=\dfrac{b+c-a}{a}+2=\dfrac{c+a-b}{b}+2\)

\(\Leftrightarrow\dfrac{a+b+c}{c}=\dfrac{a+b+c}{a}=\dfrac{a+b+c}{b}\) (* )

Từ (*) => xảy ra 2 trường hợp : \(\left\{{}\begin{matrix}a=b=c\\a+b+c=0\end{matrix}\right.\)

Xét TH1 : Khi \(a=b=c.\)

\(b=\left(1+\dfrac{a}{a}\right)\left(1+\dfrac{a}{a}\right)\left(1+\dfrac{a}{a}\right)=2.2.2=8\)

Xét TH2 : Khi \(a+b+c=0\) \(\Rightarrow\left\{{}\begin{matrix}a+b=-c\\b+c=-a\\c+a=-b\end{matrix}\right.\)

\(b=\left(\dfrac{a+b}{a}\right)\left(\dfrac{a+c}{c}\right)\left(\dfrac{b+c}{b}\right)=\left(\dfrac{-c}{a}\right)\left(\dfrac{-b}{c}\right)\left(\dfrac{-a}{b}\right)=-1.\)

Bình luận (0)